Impact of tobacco tax increases and industry pricing on smoking behaviours and inequalities: a mixed-methods study - Timea R Partos; Rosemary Hiscock; Anna B Gilmore; J Robert Branston; Sara Hitchman; Ann McNeill (NIHR Journals Library, 2020)
Background: Increasing tobacco prices through taxation is very effective for reducing smoking prevalence and inequalities. For optimum effect, understanding how the tobacco industry and smokers respond is essential. Tobacco taxation changes occurred in the UK over the study period, including annual increases, a shift in structure from ad valorem to specific taxation and relatively higher increases on roll-your-own tobacco than on factory-made cigarettes. Objectives: Understanding tobacco industry pricing strategies in response to tax changes and the impact of tax on smokers' behaviour, including tax evasion and avoidance, as well as the effect on smoking inequalities. Synthesising findings to inform how taxation can be improved as a public health intervention. Design: Qualitative analysis and evidence synthesis (commercial and Nielsen data) and longitudinal and aggregate cross-sectional analyses (International Tobacco Control Policy Evaluation Project data). Setting: The UK, from 2002 to 2016. Data sources and participants: Data were from the tobacco industry commercial literature and retail tobacco sales data (Nielsen, New York, NY, USA). Participants were a longitudinal cohort (with replenishment) of smokers and ex-smokers from 10 surveys of the International Tobacco Control Policy Evaluation Project (around 1500 participants per survey). Main outcome measures: (1) Tobacco industry pricing strategies, (2) sales volumes and prices by segments over time and (3) smokers' behaviours, including products purchased, sources, brands, consumption, quit attempts, success and sociodemographic differences. Review methods: Tobacco industry commercial literature was searched for mentions of tobacco products and price segments, with 517 articles extracted. Results: The tobacco industry increased prices on top of tax increases (overshifting), particularly on premium products, and, recently, the tobacco industry overshifted more on cheap roll-your-own tobacco than on factory-made cigarettes. Increasingly, price rises were from industry revenue generation rather than tax. The tobacco industry raised prices gradually to soften impact; this was less possible with larger tax increases. Budget measures to reduce cheap product availability failed due to new cheap factory-made products, price marking and small packs. In 2014, smokers could buy factory-made (roll-your-own tobacco) cigarettes at real prices similar to 2002. Exclusive roll-your-own tobacco and mixed factory-made cigarettes and roll-your-own tobacco use increased, whereas exclusive factory-made cigarette use decreased, alongside increased cheap product use, rather than quitting. Quitting behaviours were associated with higher taxes. Smokers consumed fewer factory-made cigarettes and reduced roll-your-own tobacco weight over time. Apparent illicit purchasing did not increase. Disadvantaged and dependent smokers struggled with tobacco affordability and were more likely to smoke cheaper products, but disadvantage did not affect quit success. Limitations: Different for each data set; triangulation increased confidence. Conclusions: The tobacco industry overshifted taxes and increased revenues, even when tax increases were high. Therefore, tobacco taxes can be further increased to reduce price differentials and recoup public health costs. Government strategies on illicit tobacco appear effective. Large, sudden tax increases would reduce the industry's ability to manipulate prices, decrease affordability and increase quitting behaviours. More disadvantaged, and dependent, smokers need more help with quitting. Future work: Assessing the impact of tax changes made since 2014; changing how tax changes are introduced (e.g. sudden intermittent or smaller continuous); and tax changes on tobacco initiation. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 8, No. 6. See the NIHR Journals Library website for further project information.